2020
DOI: 10.1515/ijfe-2019-0382
|View full text |Cite
|
Sign up to set email alerts
|

Research on the application of liquid-liquid extraction-gas chromatography-mass spectrometry (LLE-GC-MS) and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) in distinguishing the Baiyunbian aged liquors

Abstract: The purpose of the study was to reveal the differences of the flavor compounds among five Baiyunbian aged liquors by liquid-liquid extraction-gas chromatography-mass spectrometry (LLE-GC-MS) and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). In optimizing the LLE parameters, an extractant, methyl tert-butyl ether, was found which has a good extract effect and has never been used for the extraction of liquor flavor substances. Then the optimized LLE method has been applied to comprehensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The GC-IMS approach was implemented to detect the flavor characteristics of food volatile compounds, which are usually employed to distinguish the odor characteristics of different samples. At present, the technique is commonly applied in meat [13,14], fruits [15,16], and wine [17]. Most of the previous studies mainly focused on the aroma and quality control and grading from food.…”
Section: Introductionmentioning
confidence: 99%
“…The GC-IMS approach was implemented to detect the flavor characteristics of food volatile compounds, which are usually employed to distinguish the odor characteristics of different samples. At present, the technique is commonly applied in meat [13,14], fruits [15,16], and wine [17]. Most of the previous studies mainly focused on the aroma and quality control and grading from food.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid-liquid extraction (LLE) method developed by Zhou was utilized for the extraction of avor compounds, with slight modi cations (Zhou et al, 2021). Firstly, 60 mL of Baijiu sample alcohol was diluted to 14% vol with ultrapure water, and sodium chloride was added to saturate the diluted Baijiu sample.…”
Section: Detection Of Characteristic Volatile Components Of Two Light...mentioning
confidence: 99%
“…Their findings demonstrated that the majority of the compounds exhibited a downward trend throughout the distillation process. Zhou et al (2021) used headspace and gas chromatography–ion mobility spectrometry (HS-GC–IMS) to establish the characteristic flavor profiles of five of Baiyunbian-aged liquors. The results indicated that the characteristic peaks of the flavor compounds in the GC–IMS 3D spectra could effectively reveal the differences in flavor compounds among five Baiyunbian-aged liquors.…”
Section: Introductionmentioning
confidence: 99%